Performance analysis of exponential‐fed perfusion cultures for pDNA vaccines production. Issue 2 (17th May 2016) - García‐Rendón, Aurora; Munguía‐Soto, Rodolfo; Montesinos‐Cisneros, Rosa M.; Guzman, Roberto; Tejeda‐Mansir, Armando
Abstract: BACKGROUND: The clinical application of plasmid DNA (pDNA) vaccines is progressing and it is essential to develop industrial bioprocesses to economically manufacture these macromolecules. In order to contribute to achieving this goal, in this work an exponential‐fed perfusion (EFP) culture for the production of pVAX1‐NH36 hosted in Escherichia coli DH5α for application as specific vaccine was investigated using a theoretical–experimental approach. RESULTS: An experimental plasmid productivity of 3.0 mg L −1 h −1 was obtained, which represent a 1.5‐fold increase in this performance criteria. A mathematical model to investigate the system performance was built and validated. A novel aspect of the study is the analysis of the influence of individual model parameters on selected output variables and on scale‐up. CONCLUSIONS: This work contributes to the design and optimization of EFP cultures for the efficient production of pDNA for therapeutic use. The higher productivity of the EFP bioprocess might reduce both capital investment and operational costs and as a result be economically attractive compared with conventional bioprocess. © 2016 Society of Chemical Industry